Vision-Related Quality of Life in Patients with Ocular Graft-versus-host Disease - Saboo, Ujwala S (Ophthalmology, 2015)
OBJECTIVE: To assess the vision-related quality of life in a cohort of patients with ocular graft-versus-host disease (GVHD). DESIGN: Prospective study. PARTICIPANTS: Eighty-four patients diagnosed with chronic ocular GVHD METHODS: We assessed the vision-related quality of life with the 25-item National Eye Institute Visual Function Questionnaire (NEI-VFQ-25). The symptoms of ocular GVHD were assessed using the Ocular Surface Disease Index (OSDI) and Symptom Assessment in Dry Eye (SANDE) questionnaires. MAIN OUTCOME MEASURES: We assessed vision-related quality of life with NEI-VFQ-25 and compared the scores obtained from patients with ocular GVHD to those from a healthy population. In the ocular GVHD population, we also evaluated the associations between the NEI-VFQ-25 and dry eye symptoms measured by OSDI and SANDE questionnaires, age, duration of disease, best-corrected visual acuity, corneal fluorescein staining, tear break-up time, and Schirmer test. RESULTS: The mean composite NEI-VFQ-25 score in patients with ocular GVHD was 76.5 ± 17. Compared to healthy subjects, ocular GVHD patients reported reduced scores on all NEI-VFQ-25 subscales (each P < 0.001) with exception of color vision (P = 0.11). The NEI-VFQ-25 composite scores significantly correlated with OSDI (R = −0.81, P < 0.001), SANDE (R = −0.56, P < 0.001), corneal fluorescein staining (R = −0.36, P = 0.001) and best-corrected visual acuity (R = −0.30, P = 0.004). CONCLUSION: Patients with ocular GVHD experience measurable impairment of vision-related quality of life. This study highlights the impact of ocular GVHD on the vision-related quality of life, and hence the importance of comprehensive diagnosis and treatment of this condition.